Upaya Orang Tua Dalam Memaksimalkan Belajar Anak Selama School Form Home Pandemi Covid-19 - Husna, Rahmatul; Adri, Zakwan (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
Since Indonesia was hit by the Covid-19 pandemic, the learning method for students has changed drastically, which was initially carried out face-to-face now to online-based learning. The inadequate use of technology in schools, especially elementary school (SD) students, makes it difficult for them to adjust to online learning. Therefore, this study aims to determine what efforts parents should make in maximizing children's learning during online learning. Researchers obtained data from 100 parents elementary school (SD) students in Kamang Magek, Kab. Agam, West Sumatra by filling out the questionnaire provided. Data analysis uses an Indigenous Psychological Approach by using several steps, namely determining phenomena that occur in society, identifying answers from respondents into sub categories, then grouping them based on the results of idenification into sub-categories, and finally grouping them in tabular form and determining the main and sub categories. more relevant categories. The results of this study indicate that on average elementary school (SD) students are less able to take part in online learning, there are many obstacles experienced by students such as less understanding of learning material, more interested in playing with friends, bad networks and quotas cause students to be lazy and the pile up of assignments given to the school. More in-depth research is needed to find out what efforts parents should make to maximize children's learning.